Covalent-driven Layer-by-layer Self-assembly of Clindamycin-loaded PPLA Nanoparticles/chitosan Membrane on Titanium Sheet for Longacting Anti-infection - Yang, Shuangya; Yin, Yan; Xu, Yajuan; Zhang, Tanglin; Li, Youbin; Fei, Jun; Huang, Xiao (Current Nanoscience, 2021)
Background: Post-arthroplasty implant-related infection is one of the most feared complications with adverse consequences for patients and public health systems, especially in terms of the huge financial cost of treatment. This is compounded by the potential risks of continuous metamorphosis and emergence of new resistant bacterial strains. Constructing an antibacterial surface, therefore, on the implant represents an approach to reduce the incidence of implant-related infections. Methods: In this study, a covalent-driven layer-by-layer self-assembly of clindamycin-loaded polyethylene glycol grafted polylactic acid nanoparticles/chitosan membrane has been successfully fabricated on the titanium sheet and evaluated for drug releasing potential and antibiotic activity. Results: Attenuated total reflectance spectrum of the layer-by-layer self-assembly membrane showed three absorption peaks around 1680, 1520 and 1240 cm-1, which are the characteristic absorption peaks of secondary amines. The results indicated the formation of an amide bond between the carboxyl groups of clindamycin-loaded polyethylene glycol grafted polylactic acid nanoparticles and the amino groups of chitosan. The covalent bond stabilized the membrane construct. The membrane exhibited a sustained drug release behavior whereby less than 50% of clindamycin was released after 160 hr. The membrane persistently inhibited the growth of Staphylococcus aureus with the inhibition ratio exceeding 60%. Conclusion: The membrane construct holds a great potential for managing anti-implant-related infections.
Keywords: long-acting bacteriostatic effect